Association of cancer progression with elevated expression of programmed cell death protein 1 ligand 1 by upper tract urothelial carcinoma and increased tumor-infiltrating lymphocyte density - Nukui, Akinori (Cancer Immunol Immunother, 2020)
BACKGROUND: Increased expression of programmed cell death 1 ligand 1 (PD-L1) by tumor cells is thought to be a mechanism through which solid cancers promote immune tolerance. However, the association between PD-L1 expression and the prognosis of upper urinary tract urothelial carcinoma (UTUC) remains unknown. METHODS: We examined immunohistochemical PD-L1 expression and the tumor-infiltrating lymphocyte density (TILD) in 79 patients with UTUC who underwent nephroureterectomy. We classified the tumors into four types based on the combination of PD-L1 expression and TILD, and studied the clinicopathological characteristics of these four tumor types. RESULTS: Elevated expression of PD-L1 by tumor cells and a higher TILD were associated with a worse histological grade, higher pT stage, and higher peripheral blood neutrophil-to-lymphocyte ratio. Elevated expression of PD-L1 by tumor cells, a higher TILD, and type I, III, or IV tumors with elevated expression of either PD-L1 or TILD showed a positive correlation with poorer differentiation and local invasion. These three variables were associated with shorter progression-free survival and overall survival in univariate analysis, but only the latter was an independent determinant according to multivariate analysis. The patients who had type II tumors with lower PD-L1 expression and a lower TILD showed more favorable survival than the other three groups. CONCLUSIONS: These findings suggest that PD-L1 expression and TILs in the tumor microenvironment influence the progression of UTUC. Accordingly, it is important to understand the immunologic characteristics of the tumor microenvironment to develop more effective treatment strategies for this cancer. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00262-020-02499-7) contains supplementary material, which is available to authorized users.